2020
DOI: 10.1097/ta.0000000000002894
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal resection in emergency general surgery: An EAST multicenter trial

Abstract: OBJECTIVE Evidence comparing stoma creation (STM) versus anastomosis after urgent or emergent colorectal resection is limited. This study examined outcomes after colorectal resection in emergency general surgery patients. METHODS This was an Eastern Association for the Surgery of Trauma-sponsored prospective observational multicenter study of patients undergoing urgent/emergent colorectal resection. Twenty-one centers enrolled patients for 11 months. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Similarly, a multicenter study of 439 patients found stoma creation, open abdomen management, and intraoperative blood transfusions linked to morbidity; additionally, preoperative vasopressor and steroid use, as well as intraoperative transfusions, were significant predictors of mortality. [11] Other research aligning with our results highlighted the significance of low serum albumin, elevated blood urea nitrogen levels, and hypotension requiring perioperative vasopressor support. [18,19] It should be noted, however, that these studies include a wider range of colorectal surgeries and patients with colonic malignancies, in contrast to the present study's focus on isolated left colon surgeries.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, a multicenter study of 439 patients found stoma creation, open abdomen management, and intraoperative blood transfusions linked to morbidity; additionally, preoperative vasopressor and steroid use, as well as intraoperative transfusions, were significant predictors of mortality. [11] Other research aligning with our results highlighted the significance of low serum albumin, elevated blood urea nitrogen levels, and hypotension requiring perioperative vasopressor support. [18,19] It should be noted, however, that these studies include a wider range of colorectal surgeries and patients with colonic malignancies, in contrast to the present study's focus on isolated left colon surgeries.…”
Section: Discussionsupporting
confidence: 85%
“…Aligning with literature, the leading non-malignant cause for surgery was diverticular disease, whose rising incidence in our population may be attributed to changes in dietary habits. [10,11] The Hartmann procedure emerged as the most frequently employed surgical technique. Key considerations in selecting the surgical approach include the patients' clinical and hemodynamic statuses, intraoperative findings, and the availability of an experienced colorectal surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Given the paucity of studies relating to emergency laparotomy closure and bundles we felt abdominal domain closure, the "Surgeon's signature", is one of the keys to laparotomy. As surgeons, we understand that technical elements are important and Aicher's recent multicentre study throws light on outcomes following emergency colorectal surgery; there was a 27.3% surgical site infection rate and 5.3% fascial dehiscence in 469 patients operated on in 21 medical centres in the US between 2018 and 2019 [56].…”
Section: Discussionmentioning
confidence: 99%
“…Primary anastomoses performed during hemodynamic instability are more likely to leak, as evidenced by trauma and acute care surgery literature. 14 However, in the setting of hemodynamic instability, often the safest option for unstable patients is an end ostomy (as opposed to anastomosis and diversion) to decrease time under general anesthesia.…”
Section: Who Leaks (And Who Doesn't Leak)?mentioning
confidence: 99%